Founder virus population related to route of virus transmission: a determinant of intrahost human immunodeficiency virus type 1 evolution? - Lukashov, V V (1997)
We and others have shown that in individual human immunodeficiency virus type 1 (HIV-1) infection, the adaptive evolution of HIV-1 is influenced by host immune competence. In this study, we tested the hypothesis that in addition to selective forces operating within the host, transmission bottlenecks have an impact on HIV-1 intrahost evolution. Therefore, we studied the intrahost evolution of the V3 region of the external glycoprotein gp120 of HIV-1 during the 3- and 5-year periods following seroconversion after parenteral versus sexual (male-to-male) transmission in 41 participants of the Amsterdam prospective cohorts of homosexual men (n = 31) and intravenous drug users (IVDUs; n = 10) who were AIDS free and had comparable numbers of CD4+ cells. We observed that HIV-1 strains in homosexual men accumulated over 5 years more nonsynonymous substitutions within the V3 loop than HIV-1 strains in IVDUs as a result of lower rates of nonsynonymous evolution in both the initial 3-year period from seroconversion and the following 2-year period as well as a larger proportion of nonsynonymous back substitutions in IVDUs. The mean numbers of synonymous substitutions did not differ between the two risk groups. Since HIV-1 strains in IVDUs could be distinguished from the viruses of homosexual men based on several nucleotide substitutions of which the most conserved is a synonymous substitution at the tip of the V3 loop (GGC pattern), we studied whether the founder virus population itself has an impact on the intrahost evolution of HIV-1. The mean number of nonsynonymous substitutions accumulated over 5 years within the V3 loop was lower in 10 IVDUs infected by the HIV-1 strains with the GGC signature than in 4 IVDUs infected by HIV-1 strains lacking this pattern, while the mean numbers of synonymous substitutions were similar in the two groups.